A high-speed fixed width floating-point multiplier using residue logarithmic number system algorithm. Issue 4 (October 2020) - Rubia, J Jency; Sathish Kumar, GA
The Residue Logarithmic Number System (RLNS) in digital mathematics allows multiplication and division to be performed considerably quickly and more precisely than the extensively used Floating-Point number setups. RLNS in the pitch of large scale integrated circuits, digital signal processing, multimedia, scientific computing and artificial neural network applications have Fixed Width property which has equal number of in and out bit width; hence, these applications need a Fixed Width multiplier. In this paper, a Fixed Width-Floating-Point multiplier based on RLNS was proposed to increase the processing speed. The truncation errors were reduced by using Taylor series. RLNS is the combination of both the residue number system and the logarithmic number system, and uses a table lookup including all bits for expansion. The proposed scheme is effective with regard to speed, area and power utilization in contrast to the design of conservative Floating-Point mathematics designs. Synthesis results were obtained using a Xilinx 14.7 ISE simulator. The area is 16, 668 µm 2, power is 37 mW, delay is 6.160 ns and truncation error can be lessened by 89% as compared with the direct-truncated multiplier. The proposed Fixed Width RLNS multiplier performs with lesser compensation error and with minimal hardware complexity, particularly as multiplier input bits increment.